2020
DOI: 10.3389/fpsyg.2020.01980
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Rhythm, Autonomic Modulation, and the Spectrum of Emotions: The Future of Emotion Recognition and Modulation

Abstract: Pulmonary ventilation and respiration are considered to be primarily involved in oxygenation of blood for oxygen delivery to cells throughout the body for metabolic purposes. Other pulmonary physiological observations, such as respiratory sinus arrhythmia, Hering Brewer reflex, cardiorespiratory synchronization, and the heart rate variability (HRV) relationship with breathing rhythm, lack complete explanations of physiological/functional significance. The spectrum of waveforms of breathing activity correlate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 72 publications
1
33
0
1
Order By: Relevance
“…The respiration patterns show a high correlation with human emotions, e.g., fast breathing may be caused excitement due to happiness, anger, or anxiety [21]. Happiness and other positive emotions have a substantial impact on respiratory changes [22,23]. The high frequency of heart rate variability is substantially influenced by respiration due to heart rate increase during inspiration and heart rate decrease during expiration, a phenomenon called respiratory sinus arrhythmia (RSA) [24,25].…”
Section: Respiration Patterns During Emotionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The respiration patterns show a high correlation with human emotions, e.g., fast breathing may be caused excitement due to happiness, anger, or anxiety [21]. Happiness and other positive emotions have a substantial impact on respiratory changes [22,23]. The high frequency of heart rate variability is substantially influenced by respiration due to heart rate increase during inspiration and heart rate decrease during expiration, a phenomenon called respiratory sinus arrhythmia (RSA) [24,25].…”
Section: Respiration Patterns During Emotionsmentioning
confidence: 99%
“…Happiness has a variable effect on breathing rate depending on how arousal one is, whilst arousing one increases the respiration rate [26]. Similarly, humans tend to suppress their breaths when having emotions of disgust [22,23]. Research also shows [22,23,27] that humans demonstrate shallower and faster breathing when facing fear.…”
Section: Respiration Patterns During Emotionsmentioning
confidence: 99%
“…In these studies, a reciprocal relationship between respiration and cognitive function was found. Respiration is affected by cognitive load 13 , 14 or emotion (stress and anxiety) 15 , which alters the depth and rhythm of breathing. Conversely, respiratory patterns affect frontal cortex and hippocampus functions and, consequently, the formation of memories 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of the cardiovascular system and respiration is influenced by cortical structures that influence the baroreflex regulation under normal conditions ( Furness, 2006 ; Duschek et al, 2013 ; Jerath and Beveridge, 2020 ) and during the development of pathologies ( Lewis et al, 2006 ; Molkov et al, 2014 ). Considerable attention of researchers is paid to the peculiarities of baroreflex regulation and autonomic control of cardiovascular system during sleep ( Brandenberger et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%